Experiments on active precision isolation with a smart conical adapter. (21st July 2016) - Li, H.; Li, H.Y.; Chen, Z.B.; Tzou, H.S.
Abstract: Based on a conical shell adaptor, an active vibration isolator for vibration control of precision payload is designed and tested in this study. Flexible piezoelectric sensors and actuators are bonded on the adaptor surface for active vibration monitoring and control. The mathematical model of a piezoelectric laminated conical shell is derived and then optimal design of the actuators is performed for the first axial vibration mode of the isolation system. A scaled conical adaptor is manufactured with four MFC actuators laminating on its outer surface. Active vibration isolation efficiency is then evaluated on a vibration shaker. The control model is built in Matlab/Simulink and programmed into the dSPACE control board. Experimental results show that, the proposed active isolator is effective in vibration suppression of payloads with the negative velocity feedback control. In contrast, the amplitude responses increase with positive feedback control. Furthermore, the amplitude responses increases when time delay is added into the control signals, and gets the maximum when the delay is close to one quarter of one cycle time.